Observation of higher-order time-dislocation topological modes - Jia-Hui Zhang; Feng Mei; Yi Li; Ching Hua Lee; Jie Ma; Liantuan Xiao; Suotang Jia (Nature Communications)
Abstract Topological dislocation modes resulting from the interplay between spatial dislocations and momentum-space topology have recently attracted significant interest. Here, we theoretically and experimentally demonstrate time-dislocation topological modes which are induced by the interplay between temporal dislocations and Floquet-band topology. By utilizing an extra physical dimension to represent the frequency-space lattice, we implement a two-dimensional Floquet higher-order topological phase and observe time-dislocation induced π-mode topological corner modes in a three-dimensional circuit metamaterial. Intriguingly, the realized time-dislocation topological modes exhibit spatial localization at the temporal dislocation, despite homogeneous in-plane lattice couplings across it. Our study opens a new avenue to explore the topological phenomena enabled by the interplay between real-space, time-space and momentum-space topology.